Phytochemical and FTIR Analysis Of Coriander Leaf Infusion As An Active Pharmaceutical Ingredient - Wulandari, Suci; Sinaga, Siti Morin; Harahap, Urip (Publisher Cv. Inara, 2023)
This study reported that the sample used in the study was an infusion using fresh coriander leaves samples taken in the Lubuk Pakam area. Several studies have shown that the active components of coriander seeds are essential oils such as sabiene, myrcene, alphaterpine, ocimene, linalool, graniol, decanal, desilaldehyde, trantridecen, petroselinic acid, octadesenic acid, d-mannite, scopoletin, psimena, kamfena and felandren. These components cause coriander to have a good effect as a medicinal component. In previous studies, Linalool is believed to have antioxidant, anxiety, antibacterial (especially gram-positive) and antifungal effects. This activity is suspected because coriander contains secondary metabolites such as alkaloids, saponins, flavonoids, tannins, steroids, triterpenoids, glycosides. So this research was conducted to determine the content of secondary metabolites in coriander leaves by phytochemical screening. Phytochemical screening is a test to determine the class of chemical compounds present in coriander leaf infusion samples. Fourier transform infrared spectroscopy (FTIR) analysis was performed to find the isolating compounds in coriander leaves. The results showed that one secondary metabolite compound was negative in examining steroid secondary metabolites. The results of extract assistance with FTIR showed the presence of saponins with a molecular weight of 873.0 g/mol at a retention time of 19,287 minutes, but the peaks produced were not dominant.